2023
DOI: 10.3389/fanim.2023.1212194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Haemonchus contortus infection on feed intake, digestion, liveweight gain, and enteric methane emission from Red Maasai and Dorper sheep

Abstract: A study was conducted with Red Maasai and Dorper lambs to evaluate the effects of infection with the gastrointestinal nematode (GIN) Haemonchus contortus on feed intake, liveweight gain (LWG), feed energy and nitrogen partitioning, and enteric methane (CH4) emissions. Six- to seven-month-old Red Maasai (n=12) and Dorper (n=12) lambs were randomly allocated to three treatments (n=8, four lambs per breed) in a 2×3 factorial cross-over study over two periods (P1 and P2) of 36 days each. The treatments consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 68 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…However, there were no effects of infection on feed intake and digestibility, nutrient partitioning, liveweight gain, or CH 4 emission. These findings confirmed previous observations in lambs infected with H. contortus (Mwangi et al, 2023). However, Mwangi et al (2023) found that LW loss by infected lambs was significantly higher and twice as high than the LW loss in uninfected lambs, similarly in the current study, the LW loss in the infected lambs fed solely on hay was 37% higher than that of their uninfected counterparts, however this difference was not statistically significant.…”
Section: Effects Of Haemonchus Contortus Infection On Animal Health F...supporting
confidence: 91%
See 4 more Smart Citations
“…However, there were no effects of infection on feed intake and digestibility, nutrient partitioning, liveweight gain, or CH 4 emission. These findings confirmed previous observations in lambs infected with H. contortus (Mwangi et al, 2023). However, Mwangi et al (2023) found that LW loss by infected lambs was significantly higher and twice as high than the LW loss in uninfected lambs, similarly in the current study, the LW loss in the infected lambs fed solely on hay was 37% higher than that of their uninfected counterparts, however this difference was not statistically significant.…”
Section: Effects Of Haemonchus Contortus Infection On Animal Health F...supporting
confidence: 91%
“…The lambs in this study, sourced from a flock kept on rangelands, had previous exposure to H. contortus and other GIN. Thus, the lack of GIN infection effect on feed intake, digestibility, and CH 4 emissions in the current study supports the hypothesis of Mwangi et al (2023) that prior exposure of lambs to GIN confers them with a degree of resilience to the negative effects of infection on feed intake and digestibility (and consequently CH 4 emission) and animal performance.…”
Section: Effects Of Haemonchus Contortus Infection On Animal Health F...supporting
confidence: 85%
See 3 more Smart Citations